Cosmetics and health: usage, perceptions and awareness (Bangladesh Journal of Medical Science, 2013)
Objectives: Cosmetics are a multi-billion dollar industry today. The present study was designed with an objective to know the extent, purpose, type and awareness for cosmetic in people's daily life in Surat city. Materials & Methods: The study was conducted among 500 randomly selected people from the Surat city through convenience sampling. All the participants were interviewed personally, using structured questionnaire. The whole study was conducted from December, to March, 2008. Results; Around 73% of the population used cosmetics for protection purpose, while only 37% used it for attraction and 19% for fashion. Only 31% checked whether cosmetic they used were tested on animals or not. 89% of the people are concerned about the brands of the cosmetic and advertisement is an important source in the selection of the cosmetics. People still prefer ayurvedic products which comprise of 44% of the total population. Only 9% of the people use the expired products suggesting that people are aware that expired products cannot be used. 77% of the people are aware about the side effects of the cosmetics. Conclusion: Overall prevalence of cosmetic product use is increasing among both males and females. Though, associated increase in awareness regarding safe use of the same was not present widely. The use of other cosmetic services like skin specialist visits, contact lenses usage is also increasing slowly. DOI: http://dx.doi.org/10.3329/bjms.v12i4.13330 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 392-397